2006
DOI: 10.1088/0953-8984/18/22/013
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption near edge spectroscopy investigations of valency and lattice occupation site of Fe in highly iron-doped lithium niobate crystals

Abstract: The oxidation state of Fe in highly doped lithium niobate crystals (2 wt% Fe2O3) in the as-grown, reduced, and oxidized states is determined by the combination of differentiation and integration methods applied to their Fe K-edge XANES (x-ray absorption near edge spectroscopy) spectra. The obtained valences are confirmed further by absorption measurements in the IR/vis (infrared and visible) spectral range. It is shown that reduction and thermo-electric oxidization of as-grown Fe:LiNbO3, respectively, leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…Results from the EXAFS analysis suggest that the iron atoms are dispersed in the LN:Fe 4 wt % crystal. This contradicts the result of Olimov et al, 7 who reported indications for formation of small iron oxide ͑Fe 2 O 3 ͒ clusters in a LN:Fe 4 wt % crystal. The crystal studied in this paper and by Olimov et al originates from the same crystal boule.…”
Section: A Exafs Analysescontrasting
confidence: 85%
See 1 more Smart Citation
“…Results from the EXAFS analysis suggest that the iron atoms are dispersed in the LN:Fe 4 wt % crystal. This contradicts the result of Olimov et al, 7 who reported indications for formation of small iron oxide ͑Fe 2 O 3 ͒ clusters in a LN:Fe 4 wt % crystal. The crystal studied in this paper and by Olimov et al originates from the same crystal boule.…”
Section: A Exafs Analysescontrasting
confidence: 85%
“…A recent x-ray absorption spectroscopy ͑XAS͒ study reported the presence of Fe 2+ and Fe 3+ atoms in iron-doped LN crystals and their incorporation into the Li site. 7 However, no site-selective structural information was provided, which would allow to differentiate between the Fe 2+ and Fe 3+ sites.…”
Section: Introductionmentioning
confidence: 99%
“…65−68 We used the integration method to determine the average oxidation state value of Fe ions. 42 The pre-edge peak A observed at the Fe K-edge XANES spectra of the STFO samples and displayed in Figure 5a is related to the 1s(Fe) → 3d(Fe) quadrupole transition, while the shoulder B corresponds to pure 1s(Fe) → 4d(Fe) dipole transition. 27 The Fe K-edge XANES spectra exhibit similar features, except for the samples with x = 0.05 and 0.11, because of the lowest iron content.…”
Section: Computational Methods and Periodic Modelmentioning
confidence: 96%
“…The average oxidation state of iron ions was estimated from Fe K-edge XANES spectra and using the integration method. 42 Fe K-edge EXAFS spectra were recorded between 7100 and 7900 eV with energy steps of 2 eV, whereas EXAFS spectra at the Ti K-edge were collected between 4880 and 5800 eV with energy steps of 2 eV. The EXAFS kχ(k) function was weighted with k 3 before carrying out the Fourier transform (FT).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the absorption edge of an element shifts toward higher energies as the valence of the atom increases. In the case of iron oxides, this was confirmed by performing X‐ray absorption near edge spectroscopy (XANES) measurements (Figure d) on iron oxide reference samples (FeO [II] and Fe 2 O 3 [III]) and comparing these with the XANES measurements of reference iron oxides in the literature . At an incident X‐ray energy of 7130 eV, all the Fe atoms are excited and this allows the recording of the total Fe K α hologram.…”
Section: Methodsmentioning
confidence: 57%